ASPECTS (Alberta Stroke Program Early CT Score) Measurement Using Hounsfield Unit Values When Selecting Patients for Stroke Thrombectomy. Issue 6 (June 2017) - Mokin, Maxim; Primiani, Christopher T.; Siddiqui, Adnan H.; Turk, Aquilla S.
Abstract : Background and Purpose—: The ASPECTS (Alberta Stroke Program Early CT Score) is a quantitate score that measures the extent of early ischemic changes. Our aim was to investigate how measurement of ASPECTS using Hounsfield unit (HU) values on initial noncontrast head computerized tomography (CT) correlates with the extent of final infarct on follow-up imaging. Methods—: Cases of acute stroke from the middle cerebral artery M1 occlusion in which complete recanalization (TICI [Thrombolysis in Cerebral Infarction] 3) was achieved were included for analysis. Using HU ratio (HU affected/HU control hemisphere) and HU difference (HU control−HU affected hemisphere) values, ASPECTS was measured on initial CT imaging and correlated with final ASPECTS at 24 hours. The study cohort consisted of 41 patients with acute stroke from the M1 occlusion. The mean time from stroke symptoms onset to baseline head CT imaging was 264 minutes and from CT to TICI 3 recanalization was 142 minutes. Results—: HU ratio within the 0.94 to 0.96 ranges showed the highest correlation coefficient and lowest mean and median errors with the final ASPECTS. The difference of 2.0 HU between the 2 hemispheres demonstrated the higher correlation coefficient ( r =0.71; P <0.0001) and the lowest mean and median absolute errors (1.4 and 1, respectively). Conclusions—: We established a simple algorithm for rapid and accurate assessment of ASPECTS on baseline CT imaging to predict the extent of final stroke in patients with emergent large vessel occlusion who undergo endovascular revascularization.